Original paperMucocutaneous warts in Middle Anatolia, Turkey: clinical presentations and therapeutic approaches - Gönül, Müzeyyen; Unal, Emine; Iyidal, Ayşegül Yalçınkaya; Çakmak, Seray; Kılıç, Arzu; Gul, Ulker; Doner, Pinar (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Introduction : Viral warts are common skin condition caused by the human papilloma virus. Aim : To determine the clinical features of warts and therapeutic approaches to warts and compare them with the literature. Material and methods : A cross-sectional survey was conducted on 362 consecutive patients presenting to a dermatology clinic in Ankara, Middle Anatolia, Turkey. Age, gender, anatomic localization, clinical types, number of warts, and medical therapy histories were recorded. Results : In our study 139 (38.4%) children and 223 (61.6%) adults had warts. Warts were seen in 191 men, and 171 women. The mean age was 24.7 ±13.5. In all groups the incidence and the number of warts were higher in men. Clinical types of warts were vulgar, anogenital, plantar, verruca plana, filiform, and mosaic. Thirty-six (9.9%) of 362 cases had more than one type. The locations of warts were as follows extremities (n = 233, 64.4%), anogenital (n = 86, 23.7%) and head and neck (n = 73, 20.2%). The incidence of anogenital warts was statistically higher in men than women (p < 0.05). Topical medical treatment was the first choice (n = 60, 57.1%). Conclusions : In our study, the incidence and the number of warts were higher in men, which is different than in previous reports. The anogenital wart (AW) was ranked second in all types of warts. According to this finding, we can say that the frequency of AW has been increased in Turkey. To our knowledge recently there have been no studies investigating the clinical features of viral warts in all ages in the literature.